2013
DOI: 10.14257/ijhit.2013.6.6.34
|View full text |Cite
|
Sign up to set email alerts
|

Impact of STBC Scheme on BER Performance Assessment of a Single Amplify and Forward Relaying Protocol Based Cooperative MIMO-OFDM System

Abstract: Cooperative communication is a novel class of wireless communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…STBC rearranges the digitally modulated data and sends to the antennas. While original and negative second conjugate data are transmitted to one antenna, another antenna receives conjugate original and second data [19].…”
Section: Introductionmentioning
confidence: 99%
“…STBC rearranges the digitally modulated data and sends to the antennas. While original and negative second conjugate data are transmitted to one antenna, another antenna receives conjugate original and second data [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a cooperative relay technique has emerged as a promising solution for the high data rate and the reliable transmission in wireless communication systems [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a lot of research efforts in analyzing the performance achieved by the cooperative relay systems (e.g., [1][2][3][4][5][6][7][8] and references therein). In [1] and [2], it was clearly shown that the cooperative relay scheme can lead to higher data rates and robustness against severe effects of fading, compared with the non-cooperative one, which is due to the cooperative diversity gain through an additional link with the relay as well as a direct link between the source and the destination nodes.…”
Section: Introductionmentioning
confidence: 99%